2017
DOI: 10.3233/jpd-171071
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy History is not Related to Parkinson’s Disease

Abstract: The results of the study suggest no effect of appendectomy on the emergence and clinical manifestations of PD. The removal of the appendix is possibly not sufficient to suppress the exposure of the brain stem to α-syn via vagal retrograde transport. Further studies are needed to elucidate the role of appendix in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…159,160 The human appendix, which houses a diverse microbiome, 161 and in which pathology-associated αSyn can be also detected, has also been suggested as a site of gastrointestinal αSyn seeding. 162 While the history of appendectomy was associated with delayed onset of PD symptoms in a small late-onset cohort 163 a larger study found no effect, 164 and others find either no effect or a slightly increased risk of developing PD 5-10 years postappendectomy. 165,166 As a reservoir of microbes and immune cells, the appendix could still have a role in modulating PD risk by influencing microbial and immune homeostasis.…”
Section: Microbiota-gut-brain Pathways In Neurodegenerative Diseasementioning
confidence: 97%
“…159,160 The human appendix, which houses a diverse microbiome, 161 and in which pathology-associated αSyn can be also detected, has also been suggested as a site of gastrointestinal αSyn seeding. 162 While the history of appendectomy was associated with delayed onset of PD symptoms in a small late-onset cohort 163 a larger study found no effect, 164 and others find either no effect or a slightly increased risk of developing PD 5-10 years postappendectomy. 165,166 As a reservoir of microbes and immune cells, the appendix could still have a role in modulating PD risk by influencing microbial and immune homeostasis.…”
Section: Microbiota-gut-brain Pathways In Neurodegenerative Diseasementioning
confidence: 97%
“…This probably does not explain the increased risk seen during a longer follow‐up period in the Svensson study, thus raising the possibility that an inflammatory response associated with appendicitis may trigger misfolded α‐synuclein in the brain. Recently, another retrospective study found that appendectomy rates were similar in PD compared to other parkinsonian conditions and controls …”
Section: Appendectomy and Risk Of Pdmentioning
confidence: 97%
“…However, whether the Appendix, as a GI tract lymphoid organ, has an enhanced capacity to generate truncated α-syn amylogenic seeds is unknown. Further studies are required to elucidate the role of Appendix in PD (Marras et al, 2016; Svensson et al, 2016; Yilmaz et al, 2017; Palacios et al, 2018).…”
Section: The Prion-like Mechanism Of Pdmentioning
confidence: 99%